2021
DOI: 10.2196/28118
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Behavioral Intentions Toward COVID-19 Vaccines: Theory-Based Content Analysis of Tweets

Abstract: Background Acceptance rates of COVID-19 vaccines have still not reached the required threshold to achieve herd immunity. Understanding why some people are willing to be vaccinated and others are not is a critical step to develop efficient implementation strategies to promote COVID-19 vaccines. Objective We conducted a theory-based content analysis based on the capability, opportunity, motivation–behavior (COM-B) model to characterize the factors influen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 37 publications
0
40
2
1
Order By: Relevance
“…We therefore wanted to evaluate the public's initial reaction and response to COVID-19 vaccination. Few prior studies have included this time frame during the analysis period [30,[34][35][36].…”
Section: Study Datamentioning
confidence: 99%
“…We therefore wanted to evaluate the public's initial reaction and response to COVID-19 vaccination. Few prior studies have included this time frame during the analysis period [30,[34][35][36].…”
Section: Study Datamentioning
confidence: 99%
“…These were referred to as Protection and Insurance. A similar type of topic classification, not into determinants but overriding themes, was done in the works [47], [52] and [49]. There are many approaches for extracting knowledge from a short text (tweets).…”
mentioning
confidence: 99%
“…Next, an iterative process of topic labeling was performed: (i) topics were labeled to create the first version of labels based on the keywords with the greatest weight, (ii) names of labels were polished through in-depth reading of the most representative topic tweets, and (iii) the final set of topic labels was created. Similar to [47], [49] and [52], our thematic approach relied on human interpretation. Thus, this approach could be significantly influenced by personal understanding of the topics and a variety of biases.…”
mentioning
confidence: 99%
“…For future work, we will perform a theory-based content analysis to gain insight into the reasons that led to the changes in behavioral intentions we noted in the temporal analysis. Using the transfer learning model in this study, researchers can automatically collect tweets containing COVID-19 vaccine–related behavioral intentions and systematically analyze the data through a theoretical model (eg, Capability, Opportunity, Motivation, Behavior model [ 12 , 46 ]) to promote timely promotion strategies. In addition, researchers can extract individual characteristics from the user profile and perform statistical analysis to determine the relationship between individual characteristics and their behavioral intention toward COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The SAGA Working Group developed the Vaccine Hesitancy Determinant Matrix, including contextual influences (ie, related to historic, sociocultural, environmental, institutional, economic, or political factors), individual and group influences (ie, factors related to personal perception or social environment), and vaccine/vaccination-specific issues [ 10 ]. Unlike other common vaccines, the COVID-19 vaccines are associated with many factors that might amplify vaccine hesitancy [ 11 , 12 ]. Previous studies have reported widespread public concern about the rapid speed of vaccine development, novelty of the development technology (mRNA), unknown long-term side effects, and politicization of vaccines [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%